PROFILE OF PATIENTS ON THE WAITING LIST FOR KIDNEY TRANSPLANTATION - Gilson de Vasconcelos Torres; Ana Elza Oliveira de Mendonça; Ingrid Gurgel Amorim; Isabelle Christine Marinho de Oliveira; Rodrigo Assis Neves Dantas; Izaura Luzia Silvério Freire (Universidade Federal de Santa Maria, 2014)
Aim: to identify the profile of patients on the waiting list for kidney transplantation. Method: descriptive and quantitative study performed from May 2010 to May 2012, with 55 patients followed at the outpatient unit of nephrology in Natal/RN, Brazil. Results: of those surveyed, 63,6% were males, 39,9 (±12,2) years median age, coming from the country (56,4%), married (60,0%), with children (50,9%). Elementary School was the predominant level of schooling (41,8%) and the majority of patients (89,1%) did not exercise any working activity. Most had monthly income up to two minimum wages (67,3%). The majority of patients in the unique waiting list were submitted to hemodialysis (98,2%), were hypertensive (81,8%) and with an average registration time of 1,9 (±1,9) years. Conclusion: to know the profile of patients is essential to plan health actions, in order to minimize the morbidity and mortality on the waiting list.